Hubungan antara Kecemasan Matematika dan Hasil Belajar Matematika Siswa - anastasia anastasia; Linda Dwi Saputri (J-PiMat : Jurnal Pendidikan Matematika, 2026)
This study aims to determine the relationship between mathematics anxiety and mathematics learning outcomes of eighth-grade students at SMP Negeri 2 Nanga Pinoh. This research employed a quantitative approach with a correlational design. The sample consisted of 48 students, selected using simple random sampling. Data on mathematics anxiety were collected using a questionnaire consisting of 20 items, while mathematics learning outcomes were measured using a test consisting of 10 questions. Both instruments had been tested for validity and reliability. The reliability test results showed that the mathematics anxiety questionnaire had a coefficient of 0.813, while the mathematics learning outcomes test had a coefficient of 0.870, indicating that both instruments were highly reliable. Data analysis was conducted using descriptive statistics and the Spearman Rank correlation test to examine the relationship between the two variables. The results showed that there was a significant negative relationship between mathematics anxiety and mathematics learning outcomes (? = -0,288; p = 0,047) with a low level of correlation. This indicates that the higher the students’ mathematics anxiety, the lower their mathematics learning outcomes tend to be.Keyword: Mathematics Anxiety, Learning Outcomes, Spearman Rank